Nanotechnology and Drug Delivery - Delcassian,D; Patel,A (Academic Press, 2019)
By covering the many different ways engineers can deliver innovative solutions to tackle cancer, this book is a valuable read for researchers who have an ambition to make an impact on people’s life in either an academic or industrial ...